2007
DOI: 10.1016/j.jtcvs.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy resistance and oncogene expression in non–small cell lung cancer

Abstract: Multi-drug chemotherapy resistance in non-small cell lung cancer tumor cultures is common, and associations between molecular markers and in vitro chemotherapy resistance are noted. Clinical validation through integration of such testing into clinical trials seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The results of biomarker testing by immunohistochemistry and flow cytometry on the primary ovarian tumor were abstracted from the database [19]. These biomarker evaluations for immunohistochemistry and flow cytometry were performed by Oncotech Inc. as part of routine clinical testing by using the fresh tumor samples obtained by pathologist at the time of primary cytoreductive surgery as described previously [20][21][22]; tumor tissues were also processed for formalin fixation for H&E staining. The H&E slides from the primary ovarian tumor specimens and metastatic sites were used for evaluation of tumoral LVSI.…”
Section: Discussionmentioning
confidence: 99%
“…The results of biomarker testing by immunohistochemistry and flow cytometry on the primary ovarian tumor were abstracted from the database [19]. These biomarker evaluations for immunohistochemistry and flow cytometry were performed by Oncotech Inc. as part of routine clinical testing by using the fresh tumor samples obtained by pathologist at the time of primary cytoreductive surgery as described previously [20][21][22]; tumor tissues were also processed for formalin fixation for H&E staining. The H&E slides from the primary ovarian tumor specimens and metastatic sites were used for evaluation of tumoral LVSI.…”
Section: Discussionmentioning
confidence: 99%
“…Results of phase II clinical trials of picoplatin have shown survival benefit in ovarian, NSCLC, and SCLC patients (20). The chemotherapeutic treatment of NSCLC by platinum agents has been hampered by rapid development of resistance (21). Consideration of picoplatin as a potential treatment for NSCLC led us to determine the role of OCT-mediated uptake in its lung cancer efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of biomarker testing by immunohistochemistry and flow cytometry on the primary ovarian tumor were abstracted from the database [19]. These biomarker evaluations for immunohistochemistry and flow cytometry were performed by Oncotech Inc. as part of routine clinical testing by using the fresh tumor samples obtained by pathologist at the time of primary cytoreductive surgery as described previously [20-22]; tumor tissues were also processed for formalin fixation for H&E staining. The H&E slides from the primary ovarian tumor specimens and metastatic sites were used for evaluation of tumoral LVSI.…”
Section: Methodsmentioning
confidence: 99%